Tumor‐targeted chemotherapy with the nanopolymer‐based drug NC‐6004 for oral squamous cell carcinoma - Endo, Kazuhira (Cancer Sci, 2013)
Cisplatin (CDDP) has been a key drug for chemotherapy in patients with head and neck squamous cell carcinoma. Nephrotoxicity is one of its adverse reactions that are dose limiting. To increase its antitumor effects and reduce such toxicity problems, polymeric micelles carrying CDDP (NC‐6004) have been developed. The present study was designed to evaluate the efficacy and safety of NC‐6004 for oral squamous cell carcinoma. In vitro antitumor activity was assayed in four oral squamous cell carcinoma cell lines. To investigate the antitumor and nephrotoxic effects of NC‐6004, nude mice bearing OSC‐19 were administered NC‐6004 or CDDP. The in vitro growth‐inhibitory effect of NC‐6004 was significantly less than that of CDDP. However, both NC‐6004 and CDDP showed equivalent antitumor effects in vivo. Mice with CDDP developed renal cell apoptosis; however, those injected with NC‐6004 were almost free of renal cell injury. Moreover, in an orthotopic tongue cancer model using OSC‐19, NC‐6004 reduced the rate of sentinel lymph node metastasis to lower than that with CDDP. In conclusion, considering the potential advantages in terms of noticeable antitumor activity, lymphatic drug delivery and reduced nephrotoxicity, NC‐6004 represents a significant structural improvement in the development of a platinum complex.